Integrating online and face-to-face approach to enhance students’ learning in a campus-based Malaysian tertiary institution - Ali, Mohd Fadzli (2020)
This is a qualitative longitudinal case study of a blended learning research conducted through iterations of action research cycles that expands over certain periods of time investigating impacts of a technology on teaching and learning. The study seeks to explore efficient and effective ways of supporting collaborative learning activities in a higher education context in Malaysia tertiary institution where the expectation is that the campus based students work in a blended mode that consists of face-to-face and online interactions. It started with evaluation studies conducted in three consecutive semesters, followed by a reconnaissance phase, research cycle 1 and 2. The limitations in the findings from each cycle were overcome with proposed interventions before starting with the following cycle. The study drew upon multiple data sources comprising the students’ online forum discussions, the students’ written reports of their face-to-face meeting, interviews with group leaders, and the researcher’s observations. The data were analysed with reference to the three sub-triangles of an activity system in which each subtriangle represents the tool, rules and roles. Pedagogic and methodology issues identified in the first cycle led to methodology and pedagogy intervention plans that informed the second action research cycle. The findings from the second cycle revealed the effectiveness of the pedagogic strategies adopted to help students to plan their move working from a face to face mode to an online one and vice-versa.